THE EFFECT OF KNOWLEDGE AND PERCEPTION ON MOTIVATION TO RECEIVE COVID-19 VACCINE AMONG GENERATIONS : Pengaruh Pengetahuan Dan Persepsi Terhadap Motivasi Melakukan Vaksinasi Covid-19 Antargenerasi - Fathia Rizqi Hafiza; Johan, Irni Rahmayani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
The vaccination program has become the most anticipated intervention in minimizing the spread of COVID-19, including in Indonesia. Individual motivation to receive COVID-19 vaccination is believed to be one of the important predictors of achieving national vaccination targets. This study aims to analyze the differences, relationships, and the effect of knowledge and perceptions toward motivation to receive the COVID-19 vaccine among generations. This study used an explanatory design and voluntary sampling method with 201 respondents from generations X, Y, and Z. This study showed a significant difference in knowledge, perception, and motivation between generations. More than half of the respondents had a moderate knowledge of vaccination. Moreover, Generation X and Generation Y respondents were more likely to have poor perceptions regarding COVID-19 vaccination and lack motivation to receive the vaccine. Meanwhile, generation Z recorded a moderate level of perception and motivation regarding vaccination. The results also showed that there was a significant correlation between respondent characteristics and knowledge and perception. The regression test results showed that family income, number of dependents, ethnicity, vaccination status, and perceptions related to vaccination significantly affected motivation to vaccinate COVID-19.